Increased complexity of mushroom body Kenyon cell subtypes in the brain is associated with behavioral evolution in hymenopteran insects. Issue 1 (December 2017) - Oya, Satoyo; Kohno, Hiroki; Kainoh, Yooichi; Ono, Masato; Kubo, Takeo
Abstract In insect brains, the mushroom bodies (MBs) are a higher-order center for sensory integration and memory. Honeybee (Apis mellifera L.) MBs comprise four Kenyon cell (KC) subtypes: class I large-, middle-, and small-type, and class II KCs, which are distinguished by the size and location of somata, and gene expression profiles. Although these subtypes have only been reported in the honeybee, the time of their acquisition during evolution remains unknown. Here we performedin situ hybridization oftachykinin-related peptide, which is differentially expressed among KC subtypes in the honeybee MBs, in four hymenopteran species to analyze whether the complexity of KC subtypes is associated with their behavioral traits. Three class I KC subtypes were detected in the MBs of the eusocial hornetVespa mandarinia and the nidificating scoliid waspCampsomeris prismatica, like inA. mellifera, whereas only two class I KC subtypes were detected in the parasitic waspAscogaster reticulata . In contrast, we were unable to detect class I KC subtype in the primitive and phytophagous sawflyArge similis . Our findings suggest that the number of class I KC subtypes increased at least twice – first with the evolution of the parasitic lifestyle and then with the evolution of nidification.